Development of a high-throughput in vitro screening method for the assessment of cell-damaging activities of snake venoms. - Matyas A Bittenbinder; Liliana Capinha; Daniel Da Costa Pereira; Julien Slagboom; Bas van de Velde; Nicholas R Casewell; Paul Jennings; Jeroen Kool; Freek J Vonk (Public Library of Science (PLoS), 2023)
Snakebite envenoming is a globally important public health issue that has devastating consequences on human health and well-being, with annual mortality rates between 81,000 and 138,000. Snake venoms may cause different pathological effects by altering normal physiological processes such as nervous transfer and blood coagulation. In addition, snake venoms can cause severe (local) tissue damage that may result in life-long morbidities, with current estimates pointing towards an additional 450,000 individuals that suffer from permanent disabilities such as amputations, contractions and blindness. Despite such high morbidity rates, research to date has been mainly focusing on neurotoxic and haemotoxic effects of snake venoms and considerably less on venom-induced tissue damage. The molecular mechanisms underlaying this pathology include membrane disruption and extracellular matrix degradation. This research describes methods used to study the (molecular) mechanisms underlaying venom-induced cell- and tissue damage. A selection of cellular bioassays and fluorescent microscopy were used to study cell-damaging activities of snake venoms in multi-well plates, using both crude and fractionated venoms. A panel of 10 representative medically relevant snake species was used, which cover a large part of the geographical regions most heavily affected by snakebite. The study comprises both morphological data as well as quantitative data on cell metabolism and viability, which were measured over time. Based on this data, a distinction could be made in the ways by which viper and elapid venoms exert their effects on cells. We further made an effort to characterise the bioactive compounds causing these effects, using a combination of liquid chromatography methods followed by bioassaying and protein identification using proteomics. The outcomes of this study might prove valuable for better understanding venom-induced cell- and tissue-damaging pathologies and could be used in the process of developing and improving snakebite treatments.